Agreement of the morphometric dimensions determined by traditional and image analysis methods for Arabian and Thoroughbred horses - N. Ünal; Y. Paksoy; Ö. F. Güngör (Archives Animal Breeding)
The aim of this method agreement study was to agree on traditional and digital measuring methods using a smartphone. For this purpose, in total, 48 purebred horses (24 Arabian and 24 Thoroughbred) were used in this study. Lengths of the head, neck, body, back, and rump; heights of the shoulder, withers, rump, and toe; widths of the head, chest, and front chest; and depths of the chest dimensions were taken from the horses to evaluate the agreement of the traditional and digital measuring method results. The results of these two methods were compared by linear regression and Bland–Altman plot analysis. The results of the digital analysis were strongly correlated with the traditional method results for Arabian and Thoroughbred horses (r=1.000, P<0.001). As a result of the Bland–Altman plot analysis, 95.2 % of the differentiation value points of Arabian horses and 94.9 % of the differentiation value points of Thoroughbred horses were within the 95 % limit-of-agreement (LOA) interval. The values of agreement indices (AIs) for Arabian horses were between 0.92 and 1.00, and the values for Thoroughbred horses were between 0.95 and 0.99. These results indicate great agreement between these two methods. The main limitations of this study are the study population and measurement regions, which are limited to defined regions. This study concludes that, although all dimensions have not been examined, the length, width, height, and depth dimensions of these horses demonstrate excellent accuracy between traditional and digital assessment methods.